2016
DOI: 10.1016/j.autneu.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-cardiac interaction in malignant ventricular arrhythmia and sudden cardiac death

Abstract: Sudden cardiac death as a result of lethal ventricular arrhythmias is a major cause of death in cardiac diseases such as heart failure and prior myocardial infarct. Activity of the autonomic nervous system is often abnormal where sympathetic activity is upregulated and vagal activity reduced in these conditions. The abnormal autonomic state has been shown to be a strong prognostic marker of increased mortality and propensity to lethal arrhythmias, for which there is no effective prevention. Research effort ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 146 publications
(134 reference statements)
0
35
0
Order By: Relevance
“…Influence of sympatho-vagal interactions on formation of arrhythmogenic substrate and creation of disorganized AF EGMs. The role of sympatho-vagal interactions in the genesis of ventricular arrhythmias has been well described, with vagal stimulation shown to attenuate sympathetic augmentation of arrhythmogenic substrate in the ventricle (30,31). More recently, sympatho-vagal interactions have been invoked in the creation of a vulnerable substrate for AF.…”
Section: Figure 9 Schematic Illustration Of Potential Mechanism Of Smentioning
confidence: 99%
“…Influence of sympatho-vagal interactions on formation of arrhythmogenic substrate and creation of disorganized AF EGMs. The role of sympatho-vagal interactions in the genesis of ventricular arrhythmias has been well described, with vagal stimulation shown to attenuate sympathetic augmentation of arrhythmogenic substrate in the ventricle (30,31). More recently, sympatho-vagal interactions have been invoked in the creation of a vulnerable substrate for AF.…”
Section: Figure 9 Schematic Illustration Of Potential Mechanism Of Smentioning
confidence: 99%
“…10 This is in keeping with the many studies demonstrating the antifibrillatory effect of vagal stimulation, which tends to accompany reflex syncope. 11 However, this may be an oversimplification. For example, episodes of arrhythmia in patients with Brugada syndrome most often occur during times of increased vagal tone, such as sleep and rest.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in body fluid load may activate baroreceptors in the carotid sinus, thus promoting sympathetic activation. Sympathetic nervous system mediators seem to shorten the ventricular refractory period and action potential duration and promote a nonuniform cardiac anisotropy which can induce the dispersion of muscle cell refractoriness (which increases susceptibility to arrhythmias) (Ng, ). Narayan, Drinan, Lackey, and Edman () observed that the acute volume overload in dogs with structurally normal hearts was able to elevate T‐wave alternans, thus influencing the occurrence of arrhythmias.…”
Section: Discussionmentioning
confidence: 99%